CLASSIFICATION OF ARRHYTHMIA UTILIZING MOBILENET-BASED DEEP LEARNING METHOD ON TWO-CHANNELS ECG DATA - Muhammad Nurtsani, Afin
Sudden Cardiac Death (SCD) is a significant public health issue worldwide, often arising due to severe complications from arrhythmias. One prevalent type of arrhythmia that serves as a reference point for cardiac conditions is Premature Contraction (PC), which is typically categorized into two subtypes: Premature Atrial Contraction (PAC) and Premature Ventricular Contraction (PVC). PACs have the potential to predict mini-strokes, while PVCs can indicate Coronary Heart Disease and tachyarrhythmias.Apart from PC, there's also Bundle Branch Block (BBB), which is divided into Left Bundle Branch Block (LBBB) and Right Bundle Branch Block (RBBB). LBBB is one of the criteria for diagnosing Myocardial